The association between generalized joint hypermobility and active horizontal shoulder abduction in 10-15 year old competitive swimmers - Junge, T.; Henriksen, P.; Andersen, H.; Byskov, L.; Knudsen, H.; Juul-Kristensen, B. (BMC Sports Science, Medicine and Rehabilitation, 2016)
Background: Increased shoulder mobility and Generalised Joint Hypermobility (GJH) are assumed to be predisposing risk factors for shoulder injuries. The association between GJH and shoulder mobility among competitive swimmers is unknown. The aim was to study the association between GJH and active horizontal shoulder abduction (AHSA) in young, competitive swimmers and to describe normative values of AHSA in this group. Methods: In total, 92 swimmers (10-15 years) without shoulder pain participated. GJH was evaluated with the Beighton Tests (BT) for joint hypermobility. Shoulder mobility was measured as maximum AHSA. A multiple regression model was used to assess associations between GJH and AHSA. Results: Overall, positive associations were found between GJH and AHSA. An increase of BT score was associated with an increase of AHSA, seen as an increased AHSA of 3.9°, 5.7° and 7.9° by BT cut off points =5/9, =6/9 and =7/9, respectively. Normative values for AHSA ranged from 40° to 52°, depending on age. Conclusions: Positive associations were found between GJH and AHSA, as maximum AHSA range increased with increasing BT scores. Due to lack of shoulder mobility tests in the BT scoring system, the AHSA test seems to be a promising supplemental test.